STRATEGI PENGEMBANGAN EKOSISTEM EKONOMI KREATIF DALAM MENDUKUNG KEBIJAKAN PARIWISATA DI KOTA TANJUNGPINANG - Ngabalin, Tenggara; Habibie, Alif Farhan; Darmawan, Eki (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2023)
This study describes the condition of the Creative Economy Ecosystem Development Strategy which should Support Tourism Policy by using a qualitative approach to analyze the strategy that the government must implement in developing the creative economy on Penyengat Island, Tanjungpinang City. This island has great potential in the creative economy sector, but it has not been fully utilized. Through in-depth interviews with various stakeholders, such as creative economy actors, government officials, and members of the local community, this research identifies effective strategies for advancing the creative economy on Penyengat Island. The research results show that the government needs to pay attention to several strategic aspects. First, the development of adequate infrastructure, including roads, access to electricity, and good communication facilities, is very important to support creative economy activities. Second, relevant training and education in the creative economy sector is needed to improve the skills and knowledge of business actors. Third, effective promotion and marketing through exhibitions, festivals and digital media can increase the visibility of Pulau Penyengat's creative products. In addition, easy and affordable access to finance, as well as supporting policies and regulations, such as protecting intellectual property rights and reducing bureaucracy, are important factors in supporting the growth of the creative economy. Collaboration and networking between creative economy actors also play an important role in expanding business opportunities and knowledge exchange. This study concludes that the government needs to adopt a holistic and integrated strategy to encourage the development of the creative economy on Penyengat Island. Thus, local potential can be optimized, employment can be created, and people's quality of life can be improved through increased income and business opportunities related to the creative economy.